Seaweed ecosystems may not mitigate CO2 emissions. (9th February 2022) - Gallagher, John Barry; Shelamoff, Victor; Layton, Cayne
Abstract: Global seaweed carbon sequestration estimates are currently taken as the fraction of the net primary production ( NPP ) exported to the deep ocean. However, this perspective does not account for CO2 from the consumption of external subsidies. Here, we clarify: (i) the role of export relative to seaweed net ecosystem production ( NEP ) for a closed system and one more likely open to subsidies; (ii) the importance of subsidies by compiling published estimates of NEP from seaweed-dominated ecosystems; and (iii) discuss their impact on the global seaweed net carbon balance and other sequestration constraints as a mitigation service. Examples of seaweed NEP ( n = 18) were sparse and variable. Nevertheless, the average NEP (−4.0 mmol C m –2 d –1 SE ± 12.2) suggested that seaweed ecosystems are a C source, becoming increasingly heterotrophic as their export is consumed. Critically, mitigation of greenhouse gas emissions was mixed relative to their replacement or baseline states, and where CO2 is supplied independently of organic metabolism and atmospheric exchange, we caution a sole reliance on NEP or NPP . This will ensure a more accurate seaweed mitigation assessment, one that does exceed their capacity and is effective within a compliance and carbon trading scheme.